Cervical Expression of Elafin and SLPI in Pregnancy and Their Association With Preterm Labor. (5th January 2015) - Itaoka, Nao; Nagamatsu, Takeshi; Schust, Danny J.; Ichikawa, Mayuko; Sayama, Seisuke; Iwasawa‐Kawai, Yuki; Kawana, Kei; Yamashita, Takahiro; Osuga, Yutaka; Fujii, Tomoyuki
<x xml:space="preserve">Abstract</x> Problem Elafin and secretory leukocyte peptidase inhibitor (SLPI) are unique among antimicrobial peptides (AMPs). This study aimed to determine the expression levels of these AMPs at the cervix during pregnancy and to investigate their association with preterm labor. Method of study Cervical epithelial cells were swabbed from normal pregnant women to evaluate the physiological expression of elafin and SLPI. Cross‐sectional analysis was conducted to compare cervical expression levels for SLPI and elafin among three women's groups, controls (n = 26), women with threatened preterm labor who delivered at term (t‐TPL, n = 23) and TPL who ended in preterm labor (p‐TPL, n = 19). Results Elafin and SLPI proteins were detected in the squamous and glandular cells of the cervix. Cervical SLPI expression levels increased over the course of pregnancy, whereas elafin levels remained unchanged. Cervical mRNA expression levels of elafin and SLPI were significantly higher in p‐TPL compared with t‐TPL and control groups. Conclusion Constitutive expression of elafin and SLPI in cervical cells during pregnancy suggests their essential roles in local tissue homeostasis and immune defense. The elevations in cervical elafin and SLPI expression in the women with preterm delivery might reflect the local response to the pathogen invasion into the cervix preceding preterm labor.